PERENCANAAN KOTA BARU BERBASIS LANSKAP EKOLOGIS DI KOTA UJOH BILANG, MAHAKAM ULU, KALIMANTAN TIMUR - Rezky Khrisrachmansyah; Siti Nurisyah; Hanni Adriani; Ina Winiastuti Hutriani (Diponegoro University, 2016)
Mahakam Ulu Regency is a new municipality that had been developed in 2012. Ujoh Bilang City is the new Capital City that planned as the Capital City of Mahakam Ulu Regency. The natural condition and local culture in this city create strong local characters. There are some natural and cultural condition in Ujoh Bilang City such as Geological Karst, fertile alluvium soil (nearby the Mahakam River), liveable Dayak culture that should be protected, and attended to the ecological landscape values. The aim of this study is to see the landscape character of Ujoh Bilang New Town and implement the ecological landscape approach which considers the bio-physics and cultural elements in developing and planning the city. The Methods in this study are include qualitative and quantitative analysis. Qualitative analysis was described by scientific description while the qualitative analysis was used for land suitability analysis with biophysics aspect such as slope, soil, geological condition, and town structure. The local culture values are also considered.